2018
DOI: 10.31436/imjm.v17i1.896
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiles of Young Adults with Acute Myocardial Infarction

Abstract: Introduction: The incidence of acute myocardial infarction (AMI) in young adults is increasing. However, a molecular study focusing on the pathophysiological changes in young AMI remains limited. This study aims to examine the proteomic profile of young adults with AMI compared to control subjects. We also hope to identify disease-specific protein biomarkers that contribute to the development of AMI in the young. Materials and Methods: Pooled plasma protein from 10 AMI patients aged 18 to 45 years and 10 age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…haptoglobin expression was upregulated in AMI compared to controls in a young adult population. 23 In this study, we added another group of subjects which was the hypertensive young adults and we found that plasma haptoglobin in AMI to be significantly higher in AMI compared to the hypertensive and control group respectively. Overall, our findings were in agreement with another study among general adult population, comparing 359 subjects with CAD and 83 control.…”
Section: Original Articlementioning
confidence: 89%
“…haptoglobin expression was upregulated in AMI compared to controls in a young adult population. 23 In this study, we added another group of subjects which was the hypertensive young adults and we found that plasma haptoglobin in AMI to be significantly higher in AMI compared to the hypertensive and control group respectively. Overall, our findings were in agreement with another study among general adult population, comparing 359 subjects with CAD and 83 control.…”
Section: Original Articlementioning
confidence: 89%